2017
DOI: 10.5424/sjar/2017151-10252
|View full text |Cite
|
Sign up to set email alerts
|

Short communication: East-West European farm investment behaviour - The role of financial constraints and public support

Abstract: The article investigated farm investment behaviour among East (Hungarian and Slovenian) and West (French) European Union farms using individual farm accountancy panel data for the 2003-2008 period. Despite differences in farm structures, except for the presence of capital market imperfections evidenced in the East, farms' investment behaviour was not substantially different. Farm gross investment was positively associated with real sales' growth. In addition, it was positively associated with public investment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
26
2
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(38 citation statements)
references
References 23 publications
8
26
2
2
Order By: Relevance
“…Bakucs et al , 2009; Benjamin and Phimister, 2002; Bierlen and Featherstone, 1998; Bojnec and Latruffe, 2011; Bokusheva et al , 2009; Hüttel et al , 2010; Kallas et al , 2012; Latruffe, 2005; Latruffe et al , 2010; Petrick, 2004a, 2004b; Zinych and Odening, 2009). However, studies that deal with Kornai's work (1979, 1980, 1986) on soft budget constraints (SBCs) in a new institutional framework in agriculture are generally limited to one country and exclude cross-country comparisons, except for Benjamin and Phimister (2002), and Fertő et al , (2017). Kornai (1979) specified that SBCs exist when a funding source – e.g.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bakucs et al , 2009; Benjamin and Phimister, 2002; Bierlen and Featherstone, 1998; Bojnec and Latruffe, 2011; Bokusheva et al , 2009; Hüttel et al , 2010; Kallas et al , 2012; Latruffe, 2005; Latruffe et al , 2010; Petrick, 2004a, 2004b; Zinych and Odening, 2009). However, studies that deal with Kornai's work (1979, 1980, 1986) on soft budget constraints (SBCs) in a new institutional framework in agriculture are generally limited to one country and exclude cross-country comparisons, except for Benjamin and Phimister (2002), and Fertő et al , (2017). Kornai (1979) specified that SBCs exist when a funding source – e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Previous research has investigated the issue of investment–cash flow sensitivity. Bakucs et al , (2009), Bojnec and Latruffe (2011), Bojnec and Fertő (2016) and Fertő et al , (2017) found evidence of capital market imperfections in Hungary and Slovenia during times of transition, but no study has focused on whether such imperfections persisted after 2007, or examined how these vary between countries with different farming structures and historical-institutional legacies. Our comparative paper thus seeks to fill this gap in micro farm-level data and the concept of SBCs (Kornai, 1979, 1980, 1986, 2001; Lizal and Svejnar, 2002; Kornai et al , 2003) using an applied econometric approach, thereby contributing to the literature about SBCs in a new institutional economics framework with a focus on different organisational forms and historical-institutional legacies that affect farm investment (Aoki, 2001; Bojnec et al , 2014; Brousseau and Glachant, 2008; Martino et al , 2017; Ménard and Shirley, 2008, 2014) in three countries – Estonia, Hungary and Slovenia.…”
Section: Introductionmentioning
confidence: 99%
“…The issue of farmers' investment behavior has been a subject of numerous research studies (Featherstone and Goodwin, 1993;Nwibo and Alimba, 2013;Lefebvre et al, 2014;Grzelak, 2015;Kusz and Gędek, 2015;Ayamaga et al, 2016;Levi et al, 2017;Ferto et al, 2017;) Original scientific paper DOI: /10.5513/JCEA01/20.4.2227 Wieliczko et al: Investment behavior of the Polish farms -is there any evidence for the...…”
Section: Introductionmentioning
confidence: 99%
“…Bakucs et al (2009), N. Zinych ir M. Odening (2009), I. Fertő et al (2012Fertő et al ( , 2017, A. Sahrbacher et al (2014) bei Š.…”
Section: ūKininkų ūKių Investicijų į žEmės ūKio Techniką Ypatumaiunclassified
“…M. Kocot (2008), I. Upῑte (2010), C. Balaceanu (2013) bei I. Fertő et al (2017) pastebi, kad, nors valstybės intervencijos į žemės ūkio sektorių egzistuoja įvairiose pasaulio šalyse nepriklausomai nuo jų išsivystymo lygio, turtingesnės šalys gerokai dažniau vykdo žemės ūkio protekcionistinę politiką. Didžiausia parama žemės ūkiui yra teikiama tokiose šalyse kaip JAV, Japonija, Kanada.…”
Section: Paramos įTaka ūKininkų ūKių Investicijoms į žEmės ūKio Technikąunclassified